The Triangular Love Representation of Edward Cullen Character in Breaking Dawn Part I Movie - Rini Rini (Compendium: Journal of Cultural, Literacy, and Linguistic Studies, 2017)
Breaking Dawn Part I is an American romantic movie which shows the love relationship between a human, vampire, and werewolf. This research paper discusses about the character of Edward Cullen on showing his affection toward his beloved one and the kind of love of the main couple of the movie. The purpose of this research paper is to analyze the extrinsic aspect of the movie. I used two methods in analyzing the extrinsic aspect. Qualitative method is used to collect the data of this paper. In analyzing the character of the movie, I used psychological approach. This paper used Triangular Theory of Love by Robert J. Sternberg to analyze the character. Based on the theory, love has three components which are intimacy, passion, and commitment. The finding of this research paper is the type of love of the main couple that is consummate love. The love relationship between Edward and Bella has all the three components of love. It depicts the complete components of love in the movie. Keywords: triangular theory of love, intimacy, passion, commitment.